Effect of Obesity-Linked FTO rs9939609 Variant on Physical Activity and Dietary Patterns in Physically Active Men and Women - Nathan R. West; James Dorling; Alice E. Thackray; Nicola C. Hanson; Samantha E. Decombel; David J. Stensel; Stuart J. Grice (Hindawi Limited, 2018)
Single nucleotide polymorphisms (SNPs) in the fat mass and obesity-associated (FTO) locus are associated with obesity, but lifestyle factors may modulate the obesity risk related to FTO. This study examined the physical activity and dietary patterns of 528 physically active white men and women (mean (SD): 34.9 (9.5) years, 26.6 (4.3) kg·m−2) carrying different risk variants of FTO SNP rs9939609. Sex, age, and anthropometric measurements (stature, body mass, and waist circumference) were self-reported using an online questionnaire, and body mass index and waist-to-height ratio were calculated. Physical activity and eating behaviour were assessed using the International Physical Activity Questionnaire (IPAQ) and Three-Factor Eating Questionnaire (TFEQ), respectively. Body mass, body mass index (BMI), waist circumference, and waist-to-height ratio were not significantly different between individuals expressing different FTO rs9939609 risk variants (all P≥0.66). The cohort was physically active (4516 (3043) total MET min·week−1), although homozygous risk allele carriers (AA) displayed higher TFEQ cognitive restraint compared with nonrisk allele carriers (TT) (ES = 0.33 and P=0.03). In conclusion, obesity-related parameters were not different in physically active individuals expressing different risk variants of FTO rs9939609, although homozygous risk allele carriers exhibited higher cognitive restraint.